Does trade openness exacerbate carbon dioxide emissions? evidence from Nigeria (2023)
High emissions of greenhouse gases components have today become a world phenomenon. In Africa, Nigeria is the second-highest emitter of greenhouse gases (GHGs), after South Africa. Carbon dioxide (CO2) emissions constitute the largest source of GHGs; hence it has become a widely discussed and researched subject. This, however, is a negative unintended consequence that has emanated from the growing interdependence of the world economies. One of the major instruments of achieving a global world which also stood as a major determinant of economic growth is trade openness. This paper, therefore, examines the impact and the relationship between trade openness on CO2 emissions in Nigeria. The method employed to achieve the stated objectives is the Autoregressive Distributed Lag (ARDL) cointegration technique, using the annual time series data sourced from the World Bank Development Indicator, 2020, for periods 1980 to 2019. The major findings from the study show that there is an insignificant positive relationship between trade openness on CO2 emissions. Also, there exists an increasing trend of CO2 emissions in Nigeria, while that of trade openness shows fluctuation for the periodic review and this depicts a high vulnerability to external shocks. With these findings, the study recommends that the Nigerian government should be more proactive and tenacious in implementing environmental and trade policies in favour of a cleaner economy. Also, the Nigerian government must become keener toward attracting only investors that will produce clean goods and not compromise on the necessity to improve environmental quality.